1991
DOI: 10.1111/j.1530-0277.1991.tb01869.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ethanol Initiation Procedures on Ethanol Reinforced Behavior in the Alcohol‐Preferring Rat

Abstract: Rats from the alcohol preferring (P) line developed at Indiana University were initiated to self-administer ethanol orally without food or water restriction using either a sucrose-fading or a secondary-conditioning procedure. Following initiation, they were tested under a variety of operant conditions to examine the ability of ethanol to reinforce lever pressing behavior. Regardless of initiation procedure, the animals maintained lever pressing behavior with ethanol reinforcement, even at ethanol concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…When the competing reinforcer was water, the rats preferred alcohol (e.g., Samson et al 1982). However, when the competing reinforcer was sucrose, responding reinforced by alcohol (e.g., 10% concentration) markedly decreased, even when the sucrose concentration was as low as 1% (e.g., Schwarz-Stevens et al 1991). Moreover, these relations were equally strong for specially bred, alcoholpreferring, P rats (Schwarz-Stevens et al 1991).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…When the competing reinforcer was water, the rats preferred alcohol (e.g., Samson et al 1982). However, when the competing reinforcer was sucrose, responding reinforced by alcohol (e.g., 10% concentration) markedly decreased, even when the sucrose concentration was as low as 1% (e.g., Schwarz-Stevens et al 1991). Moreover, these relations were equally strong for specially bred, alcoholpreferring, P rats (Schwarz-Stevens et al 1991).…”
Section: Introductionmentioning
confidence: 88%
“…However, when the competing reinforcer was sucrose, responding reinforced by alcohol (e.g., 10% concentration) markedly decreased, even when the sucrose concentration was as low as 1% (e.g., Schwarz-Stevens et al 1991). Moreover, these relations were equally strong for specially bred, alcoholpreferring, P rats (Schwarz-Stevens et al 1991). In an effort to develop a procedure in which alcoholic drinks remained potent reinforcers relative to sucrose and other caloric sources, experiments with sweetened alcohol were initiated (e.g., Heyman and Oldfather 1992;Heyman 1993;Petry and Heyman 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Numerous reviews of the literature (e.g., Cicero, 1979;Dole, 1986;Lester & Freed, 1973) and a multitude of experiments (e.g., Meisch & Thompson, 1973;Samson, 1986;Samson, Pfeffer, & Tolliver, 1988;Schwarz-Stevens, Samson, Tolliver, Lumeng, & Li, 1991) have demonstrated the difficulty in establishing oral self-administration of ethanol in rats. Most studies that have been able to induce substantial amounts of ethanol consumption have found that intake is related to caloric properties and rapidly dissipates with the introduction of an alternative food source (e.g., Meisch & Thompson, 1973;Schwarz-Stevens et al, 1991). In one experiment, however, Roehrs and Samson (1981) found demand for ethanol to be inelastic when it was concurrently available with water.…”
Section: Experiments 5: Simultaneous Increases In Vr Requirements For mentioning
confidence: 99%
“…Specifically, Indiana alcohol-preferring (P) (e.g., Files et al, 1992Files et al, , 1993Murphy et al, 1989;Penn et al, 1978;Ritz et al, 1994a,b;Samson et al, 1998;Schwarz-Stevens et al, 1991), ALKO alcohol-accepting (AA) (Files et al, 1997;Sinclair, 1989, 1990;Ritz et al, 1986Ritz et al, , 1989a, and Indiana high-alcohol-drinking (HAD) (Ritz et al, 1994a,b;Samson et al, 1998) rats have been described to press a lever to obtain pharmacologically relevant amounts of ethanol, in most cases comparable with those consumed under the home cage, two-bottle regimen. In contrast, selectively bred ethanol-nonpreferring Indiana alcoholnonpreferring (NP), ALKO alcohol nonaccepting (ANA), and Indiana low-alcohol-drinking (LAD) rats have been reported to display minimal degrees of lever pressing for ethanol, consistent with their avoidance of the ethanol solutions under the two-bottle paradigm.…”
mentioning
confidence: 99%